(untitled) (Research, Society and Development, 2020)
Gamification consists of involving game mechanisms in teaching with the aim of producing more student engagement in task production. Attentive to this, it was used, in Architecture and Urbanism course, in the Urban and Regional Planning course, the Gamification to deal with part or the course content. The game was developed from a didactic experience proposed and published by Silva et al. (2016). From that experience, adaptations were made to effectively mark the activity as a game. The game named “Producing agents of the city” aimed to present to the students how city agents are diverse and how they directly interfere in their construction, explaining how public and private interests divergent mold the urban space. For this purpose, it was elaborated script, characterization, currency printing and a base map for the insertion of information. Thus, the teams are agents, each one with their goal to be achieved through negotiation with the others, always drawing up an action plan based on bibliographic researches. At the end, questions related to the issues were applied to verify the effective learning and related to the methodology. Analyzing the answers, it was possible to observe that the experience was positive, because students, from the moment they are competing, they feel more motivated to research and participate in class; however, they felt difficulty in answering content matters, because, eventually, they did not make enough research to support the game.